Evaluación del desempeño ambiental del frigorífico de Zipaquirá (2017)
This monograph exposes the strategic plan of the Refrigeration Company of Zipaquirá; The environmental guidelines described in the Internal Environmental Management Program called PIGA, are the basis for diagnosing the current situation of the company against current legislation. Complementing this diagnosis, the critical environmental points are identified and analyzed, critical environmental points are evaluated and measures are proposed for the environmental management of the identified. Finally, a comparison is made between the activities outlined in the PIGA, the percentage of completion of these activities and their levels of compliance with current environmental legislation.